The Influence of Return On Assets, Return On Equity, Debt Equity Ratio on Dividend Policy of Pharmaceutical Companies Listed on the Indonesia Stock Exchange Period 2014-2017 - Eka Septa Kurniawan; Agus Sukoco; Joko Suyono (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2019)
This study aims to analyze the effect of Return On Assets , Return On Equity , Debt Equity Ratio on policies in viden. The study of retrieving data from financial statements of pharmaceutical companies that have been listed on the Indonesia Stock Exchange for the period 2014 - 2017. This type of research used in this research is quantitative research. The data collection technique used in this research is the documentation data collection technique, a measuring instrument to find out the company's dividend policy in this study, which is using Dividend Pay o ut Ratio . From the results of this study it can be concluded that the ROA, ROE, and DER that we call the independent variable (X) have a significant effect and are positive for the DPR or what we call the dependent variable (Y).